The Mediterranean diet and risk of type 2 diabetes in Iranian population - Khalili-Moghadam, Sajjad; Mirmiran, Parvin; Bahadoran, Zahra; Azizi, Fereidoun (European journal of clinical nutrition, 2019)
Background/objectives Type 2 diabetes (T2D) is fast increasing in recent decades. Limited prospective studies are available on Mediterranean diet protective effect against T2D development. We assessed longitudinal association of the Mediterranean diet with T2D risk in Iranian men and women. Subjects/methods Diet was measured using a 168-item food frequency questionnaire in 2139 adults (free of T2D), aged 20−70 years. All individuals, based on the traditional Mediterranean diet score (MDS), received scores between 0 and 8 points. Multivariate hazard ratio (HR) and 95% confidence interval (CI) were reported for the association of T2D and the MDS, with adjustment of diabetes risk score (DRS) and dietary energy intakes. Results During follow-up, a total of 143 events occurred. Individuals who had higher intakes of fish/sea foods, legumes, nuts, and monounsaturated fatty acids (MUFAs) to saturated fatty acids (SFAs) ratio had a decreased risk of T2D. After adjustment for confounders, an inverse association was found between adherence to the MDS and T2D (HR = 0.48; 95% CI 0.27−0.83). Conclusions Our findings demonstrated an inverse association between the Mediterranean diet score and incidence of T2D.